Aplikasi Pemesanan Kue dan Roti Berbasis Mobile Pada Lamonde Palembang - Supratman, Edi; Ubaidillah, Ubaidillah (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
Technology in buying and selling can be utilized to increase company profits. PT. Palembang Berkah Bersama was established in April 2017 with the business brand Lamonde Palembang, a business venture making cakes and bakeries. The product ordering process takes a long time because consumers must come to the Lamonde Palembang store or type via WA or telephone. Hence, the shop assistant has a little difficulty in recapitulating data if there is an order simultaneously. Based on interviews conducted by researchers with Mr. Erik, Marketing Manager of Lamonde Palembang, the daily sales turnover is around 60-80 pieces of cake and bread. Therefore, what is needed by Lamonde Palembang is an ordering system where the system is used to handle the ordering process online. With this system, it will be easier for consumers to order products because they can directly choose the products provided, where there are also prices for each product. The total cost of the order also appears to be well and can be determined quickly. Shop assistants can also more easily see and list orders and product sales